Nutritional status among young adolescents attending primary school in Tanzania: contributions of mid-upper arm circumference (MUAC) for adolescent assessment - Margaret Lillie; Isaac Lema; Sylvia Kaaya; Dori Steinberg; Joy Noel Baumgartner (BMC, 2019)
Abstract Background Adolescence is a critical time of development and nutritional status in adolescence influences both current and future adult health outcomes. However, data on adolescent nutritional status is limited in low-resource settings. Mid-upper arm circumference (MUAC) has the potential to offer a simple, low-resource alternative or supplement to body mass index (BMI) in assessing nutrition in adolescent populations. Methods This is secondary data analysis, from a cross-sectional pilot study, which analyses anthropometric data from a sample of young adolescents attending their last year of primary school in Pwani Region and Dar es Salaam Region, Tanzania (n = 154; 92 girls & 62 boys; mean age 13.2 years). Results The majority of adolescents (75%) were of normal nutritional status defined by BMI. Significantly more males were stunted than females, while significantly more females were overweight than males. Among those identified as outside the normal nutrition ranges, there was inconsistency between MUAC and BMI cut-offs. Bivariate analyses indicate that BMI and MUAC show a positive correlation for both female and male participants, and the relationship between BMI and MUAC was more strongly correlated among adolescent females. Conclusions Further studies are needed with more nutritionally and demographically diverse populations to better understand the nutritional status of adolescents and the practical contribution of MUAC cut-offs to measure adolescent nutrition.